The answer depends on the value of y.
For example, when y = 0, 8y2 + 6y - 2 = -2
when y = 1, it is 12
8y-7x
9y-3y=6y; 6y+2y=8y; so your answer is 8y
8y squared + 52y - 180
y = -1
Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals".
8y-7x
9y-3y=6y; 6y+2y=8y; so your answer is 8y
6y + 5
6y-8y = -2
7
-2
8y squared + 52y - 180
y = -1
Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals".
The given algebraic expression can be simplified to: 14y+4x
12y + 2 or 2*(6y+ 1)
-6